Transforming the Role of LAMDIK in Quality Assurance of Islamic Higher Education in the Global Era - Buhori Muslim; Jailani Jailani; Nurullah Nurullah; Tarmizi Ninoersy; Safrul Muluk; M. Ridha; Tabrani ZA (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2026)
This study discusses the transformation of the role of the Independent Education Accreditation Agency (IEAA/LAMDIK) in ensuring the quality of education study programmes at Islamic Higher Education Institutions (IHEI/PTKI) in the global era. This study stems from the need for reform in the quality of Indonesian higher education amid the challenges of globalisation, digitalisation, and the demands of 21st-century competencies. LAMDIK serves as an independent accreditation agency that plays a strategic role in ensuring external quality, replacing the role of National Accreditation Agency for Higher Education (NAA-HE/BAN-PT) for education clusters, with a new paradigm of accreditation based on Outcome-Based Education (OBE). The objectives of this study are to describe the transformation of LAMDIK's role, analyse the implementation of outcome-based accreditation policies, and identify the challenges faced by PTKI in the accreditation process. The method used is a multi-case qualitative approach involving three PTKIs: Universitas Islam Negeri (UIN) Ar-Raniry Banda Aceh, Universitas Islam Negeri (UIN) North Sumatra, and Sekolah Tinggi Agama Islam (STAI) Aceh Tamiang. Data were collected through in-depth interviews, observations, and documentation studies, and analysed using the Miles, Huberman & Saldana model. The study results show that LAMDIK has undergone a paradigmatic transformation in policies, instruments, and the accreditation process, from a compliance-based system to a performance- and achievement-based system. LAMDIK acts as a quality regulator, facilitator of a culture of quality, and catalyst for change in academic governance at PTKI. However, challenges remain, such as limited human resources, digital literacy, and the integration of Islamic epistemology into accreditation instruments. In conclusion, LAMDIK has become an agent of transformation in the quality of higher education in PTKI, which assesses administrative compliance and builds a sustainable quality culture oriented towards global competitiveness.